2010
DOI: 10.1074/mcp.m110.001289
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics of Caveolin-1-regulated Proteins

Abstract: Caveolae are organelles abundant in the plasma membrane of many specialized cells including endothelial cells (ECs), epithelial cells, and adipocytes, and in these cells, caveolin-1 (Cav-1) is the major coat protein essential for the formation of caveolae. To identify proteins that require Cav-1 for stable incorporation into membrane raft domains, a quantitative proteomics analysis using isobaric tagging for relative and absolute quantification was performed on rafts isolated from wild-type and Cav-1-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 59 publications
1
18
0
2
Order By: Relevance
“…Justificando a maior expressão da caveolina -1 em relação à caveolina -2, Deurs et al (2003), Dávalos et al (2010), Hansen & Nichols (2010) afirmam que a expressão das caveolina -1, a principal proteína de revestimento da cavéola, é necessária para a estruturação da cavéola, em células não musculares, já a caveolina -3 faz parte da biogênese da cavéola presente na musculatura cardíaca e esquelética à medida que somente a presença da caveolina -2 não induz a sua formação. Ainda é fundamental a presença da proteína caveolina -1 na cavéola para que a proteína caveolina -2 seja enviada do complexo de Golgi para a mesma, caso contrário a caveolina -2 seria degradada no próprio complexo de Golgi (Okamoto et al 1998, Razani et al 2001.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Justificando a maior expressão da caveolina -1 em relação à caveolina -2, Deurs et al (2003), Dávalos et al (2010), Hansen & Nichols (2010) afirmam que a expressão das caveolina -1, a principal proteína de revestimento da cavéola, é necessária para a estruturação da cavéola, em células não musculares, já a caveolina -3 faz parte da biogênese da cavéola presente na musculatura cardíaca e esquelética à medida que somente a presença da caveolina -2 não induz a sua formação. Ainda é fundamental a presença da proteína caveolina -1 na cavéola para que a proteína caveolina -2 seja enviada do complexo de Golgi para a mesma, caso contrário a caveolina -2 seria degradada no próprio complexo de Golgi (Okamoto et al 1998, Razani et al 2001.…”
Section: Discussionunclassified
“…Dávalos et al (2010) completou dizendo que as cavéolas são micro estruturas encontradas de forma abundante na membrana plasmática de muitas cé-lulas especializadas, incluindo células endoteliais, células epiteliais, e adipócitos. Com a microscopia atual, pode-se notar que há variedade morfológica destas estruturas de membranas, podendo assim estar dispostas em grupos denominados "rosetas" e/ou "cachos de uvas.…”
Section: Introductionunclassified
“…Today, this paradigm in RBC remains unchanged. However we 3 , and others 4,5 , have demonstrated that Hbα is expressed in the blood vessel wall but in contrast to other globins in the blood vessel wall 3,6,7 , Hbα localization and physiological effects are concentrated at myoendothelial junctions (MEJs) in the endothelial cells (EC) lining the lumen of blood vessels.…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have shown that the genetic loss of Cav-1 destabilizes caveolin-2 (Cav-2) and to a lesser extent destabilizes the caveolin adaptor, Cavin-1 7, 9, 29 . Interestingly, Cav-1-F92A expression in EC enhances Cav-2 and Cavin-1 levels in whole lung lysates from transgenic mice (Figure 3A) demonstrating that Cav-1-F92A does not impair caveolae integrity, but likely stabilizes the protein complex.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these findings, it is well known, that Cav-1 KO animals exhibit both pulmonary and cardiac fibrosis 7, 30, 31 and altered signaling 7 . A robust readout of caveolae formation and function is measuring the Cav-2 protein level and to a lower extent Cavin-1, as both proteins are in a stable protein complex with Cav-1, and the loss of Cav-1 genetically destabilizes endogenous Cav-2 and Cavin-1 7, 9, 29 . Whole lung or cardiac lysates show that EC expression of Cav-1-F92A indeed increased Cav-2 protein levels, suggesting that the point mutant F92A isoform did not disrupt the integrity of caveolae.…”
Section: Discussionmentioning
confidence: 99%